The control of adult neural stem cell proliferation and cognition by valproic acid - Umka, Jariya. (2010)
Valproic acid (VPA) is extensively used for the treatment of epilepsy. This drug also functions as an inhibitor of histone deacetylase enzymes and causes the expression of growth arrest genes. It has been reported that mild to moderate cognitive impairments occur in adult patients taking VPA. This investigation aimed to examine the relationship between cognition and changes in cell proliferation within the rat hippocampus, a brain region where continued formation of new neurons is associated with learning and memory. Also, the antiproliferative function of VPA was investigated in rat and mouse hippocampal neural stem cells (NSCs) and cancer cell lines in vitro.